Mechanical Approach to Analyzing Thermal Comfort in Shopping Mall Buildings - Kuscahyono; Budiyanto, Hery; Santoso, Imam (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Mechanical Approach to Analyzing Thermal Comfort in Shopping Mall Buildings